EFISIENSI PENGGUNAAN METODE HOT TAPPING PADA JALUR PIPA GAS PT XYZ DI BEKASI - Maulana, Sandio; Oscar Haris; Muhamad Arifin Rizal; aqil Rivaldi; Agus Darmawan; Muhamad Rapli Nurulazmi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
Pipa owned by PT. XYZ located in TambunBekasi is a gas pipeline 8 "along 35 km of gas from BabelanBekasi towards TegalGedeCikarang where the consumers of gas use is one of the Power Plants for Industrial Estates. The pipe passes through several river crossings, provincialroads and also residential areas. With the Government program on the planned construction of the Container Port in the Babelan area of Bekasi, the pipes belonging to PT. XYZ must be made new, and relocated again to theaccess under the river that the container ship will pass. To support the program, PT. XYZ performs data collection on the operating pipeline and also calculates the costs forthe shutdown method and without shutdown. The resultsof this study indicate that the condition of the pipe is in a safe condition and is ready for the Hot tapping method. Based on calculations according to API 570 standards and ASME B31.8 the pipeline can still operate up to a maximum pressure of 1325 psi, and the calculation of pipe life is up to 38 years. Whereas in terms of economics the method without shutdown only costs USD 204,892, - compared to the shutdown method of USD 2,087,187, -The end result is that it can be seen that the non-shutdown method is more efficient than the shutdown method on the gas pipeline in terms of costs as well as capital returns or ROI (Return of Investment) up to 95% and has a new pipeline network for adding potential customers who can increase income PT. XYZ.